Locally Interested : Institute of Contemporary Art - Sofia - Boubnova, Iara; Solakov, Nedko; National Gallery for Foreign Art, Sofia (Sofia : Institute of Contemporary Art, 1999)
Gordon, Douglas ; Kogler, Peter ; Kulik, Oleg ; Rist, Pipilotti ; Solakov, Nedko ; Tiravanija, Rirkit ; Tzaig, Uri
National Gallery for Foreign Art, Sofia, 27 October - 27 November 1999
kunstcatalogus
Keywords: Bulgarije